2004
DOI: 10.1063/1.1689755
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the potential within a nanoscale undoped GaAs region using a scanning electron microscope

Abstract: Semiconductor dopant profiling using secondary electron imaging in a scanning electron microscope (SEM) has been developed in recent years. In this paper, we show that the mechanism behind it also allows mapping of the electric potential of undoped regions. By using an unbiased GaAs/AlGaAs heterostructure, this article demonstrates the direct observation of the electrostatic potential variation inside a 90nm wide undoped GaAs channel surrounded by ionized dopants. The secondary electron emission intensities ar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 15 publications
1
24
0
Order By: Relevance
“…The first demonstration was reported by Chang and Nixon, revealing a measurable change in the secondary electron yield across a p-n junction3. Later, Kaetsner et al 4. used SEM to report on a direct observation of the potential variations inside a 90 nm GaAs channel5, and Li et al .…”
mentioning
confidence: 99%
“…The first demonstration was reported by Chang and Nixon, revealing a measurable change in the secondary electron yield across a p-n junction3. Later, Kaetsner et al 4. used SEM to report on a direct observation of the potential variations inside a 90 nm GaAs channel5, and Li et al .…”
mentioning
confidence: 99%
“…Although contrast mechanisms for the SE collection are undoubtedly due to multiple factors, and are not fully understood, they have been shown to include an influence of the surface potential [12][13][14]. By collecting images for varying values of Vrev, the change in surface potential with Vrev can be identified.…”
Section: Resultsmentioning
confidence: 99%
“…It was shown that the emission sensitivity to the material work function can be used to obtain electrostatic potential distribution inside doped semiconductor devices. 1 A higher spatial resolution, though, can be achieved in a transmission electron microscope ͑TEM͒ using off-axis electron holography. 2 With this method, a two-dimensional potential distribution inside a 0.18 m transistor was shown.…”
Section: Introductionmentioning
confidence: 99%